Critical crystallization properties of an industrial-grade Zr-based metallic glass used in additive manufacturing. (1st July 2021) - Sohrabi, Navid; Schawe, Jürgen E.K.; Jhabvala, Jamasp; Löffler, Jörg F.; Logé, Roland E.
Abstract: The major challenge to overcome when processing metallic glasses (MGs) is to avoid crystallization. Therefore, time-temperature-transformation (TTT) diagrams are used, but they are often derived from experiments in which heating or cooling rates are limited and do not cover the full range of processing conditions, especially those encountered in additive manufacturing (AM) where the rates are very high. Here, an industrial-grade Zr-based MG (AMZ4) is investigated via fast differential scanning calorimetry (FDSC). The critical cooling and heating rates of AMZ4 are experimentally measured and TTT diagrams are determined upon heating and cooling. The critical heating rate of 45, 000 K/s is 18 times the critical cooling rate, which indicates the presence of a self-doped glass (SDG) that includes quenched-in nuclei. The results illustrate that AMZ4 is very sensitive to crystallization, even in laser-based AM conditions, where heating and cooling steps need to be distinguished. Graphical abstract: Image, graphical abstract